Penghematan Listrik Rumah Tangga dalam Menunjang Kestabilan Energi Nasional dan Kelestarian Lingkungan - Santoso, Arif Dwi; Salim, Muhammad Agus (Jurnal Teknologi Lingkungan, 2019)
ABSTRACTThe government efforts to maintain national energy stability program through the increase energy supply and saving must be supported by all levels of society. Several energy observers and experts stated that the contribution of the domestic or household sector in the activities of energy saving program is quite significant because the percentage of household customers are relatively high. This paper analyzes the potential of providing research data on the percentage of electricity savings in the domestic or household sectors towards saving electricity nationally. The results of the study show that electrical devices commonly used in households still have the potential to be saved. Electrical devices that are often used at households and have great saving potentials are air conditioners and refrigerators. If each household customer saves 30% of electricity consumption, then the national electricity supply that can be saved will be around 5,679 GW, equivalent to 83.3 trillion rupiah. The saving program resulted in savings of electricity consumption of around 6% of all household consumers or around 2.9% of total national electricity consumption.Keywords: electrical energy, savings, households ABSTRAKUpaya pemerintah dalam menjaga kestabilan energi nasional melalui program peningkatan pasokan dan penghematan energi harus didukung oleh seluruh lapisan masyarakat. Para pengamat dan pakar energi menyatakan bahwa kontribusi sektor domestik atau rumah tangga dalam program penghematan konsumsi energi listrik cukup signifikan karena persentase jumlah pelanggan rumah tangga yang relatif tinggi. Penelitian ini menganalisis tentang potensi persentase penghematan energi listrik sektor domestik atau rumah tangga terhadap penghematan listrik secara nasional. Hasil penelitian menunjukkan bahwa piranti listrik yang biasa digunakan pada rumah tangga masih memiliki potensi untuk dilakukan penghematan. Piranti listrik yang sering digunakan pada rumah tangga dan memiliki potensi penghematan yang besar adalah alat pendingin ruangan (AC) dan kulkas. Bila setiap pelanggan rumah tangga melakukan penghematan konsumsi energi listriknya sebesar 30%, maka pasokan listrik nasional yang dapat dihemat adalah sekitar 5.679 GW atau setara dengan 83,3 Trilyun rupiah. Upaya ini menghasilkan penghematan konsumsi listrik sekitar 6% dari seluruh konsumen rumah tangga atau sekitar 2,9 % dari total konsumsi energi listrik nasional.Kata kunci: energi listrik, penghematan, rumah tangga